Comparison of In-Person and Virtual Labs/Tutorials for Engineering Students Using Blended Learning Principles - Maren Schnieder; Sheryl Williams; Sourav Ghosh (MDPI AG, 2022)
The paper compares the effectiveness of in-person and virtual engineering laboratory sessions. The in-person and virtual laboratory sessions reported here comprise six experiments combined with short tutorials. The virtual lab combined enquiry-based learning and gamification principles. The integration of the virtual labs with in-person teaching created a blended learning environment. The effectiveness of this approach was assessed based on (i) the student feedback (i.e., a questionnaire with open-ended questions and Likert scale feedback), (ii) the students' engagement with the virtual lab, and (iii) the impact on the academic performance (i.e., class test results). The students reported greater confidence in the understanding of theory in the virtual lab than the in-person lab. This is interesting given that the instruction for the virtual lab and the in-person lab of one experiment is identical (i.e., same instructor, same enquiry-based learning techniques, and same explanations). The students also appreciated the ability to complete the virtual lab anytime, anywhere, for as long as they needed, and highlighted the benefits of the interactivity. The median class test scores of the students who completed some or all the virtual lab experiments was higher than those who did not (83-89% vs. 67%).